Behavioral Diversity (Ethodiversity): A Neglected Level in the Study of Biodiversity - Cordero-Rivera, Adolfo (Frontiers in Ecology and Evolution, 2017)
The concept of biodiversity embraces a multifaceted and hierarchical analysis of the complexity of life, with implications in many areas of science, philosophy, ethics, politics and even religion. Three levels are included in the commonly accepted definitions: genetical, species and ecosystem diversity, going from the intraspecific level to the landscape. Here I argue that a fourth level, never included in biodiversity studies, is of prominent relevance: ethological diversity or “ethodiversity”. There is a growing number of studies describing alternative behaviours, behavioural plasticity, learning and even personality, as characteristics of animal populations or individuals. Ethodiversity is also relevant in unravelling cryptic biodiversity, such as species that differ in their behaviour but are otherwise undistinguishable. Maintaining ethodiversity is therefore essential in conservation, and cannot be achieved simply by focusing on genetic diversity. Behaviour has profound ecological consequences, particularly in species interactions, and is a crucial element in the adaptability of animals to new environments. Ethodiversity is important at the intraspecific, inter-population, and species level and has practical relevance in several fields, like captive breeding, eco-novelty and popular science. Finally, I expect ethodiversity to show a latitudinal cline, with more diverse and elaborate behaviours per species in the tropical regions, given the increase in interactions near the equator.